Teaching Figurative Expressions Through Pictures - DjumambetovaDilfuza Kongratbaevna, XadjievaDilbar Tadjimuratovna (International Journal of Advanced Science and Technology, 2020)
Figurative expressions plays an important role in both personal and professional life. However, figurative expression tasks have proven to be a challenging for students. Forthis current research, guessing the meaning of figurative expressions from pictures strategywas implemented in English language and literature department at Karakalpak state University. A pre-test, a post-test and a survey were collected to determinehow the implementation of the technique affected student’ comprehensionskill.